Targeted chitosan nanobubbles as a strategy to down-regulate microRNA-17 into B-cell lymphoma models - Capolla, Sara; Argenziano, Monica; Bozzer, Sara; D’Agaro, Tiziana; Bittolo, Tamara; De Leo, Luigina; Not, Tarcisio; Busato, Davide; Dal Bo, Michele; Toffoli, Giuseppe; Cavalli, Roberta; Gattei, Valter; et al. (Frontiers in Immunology, 2023)
Introduction: MicroRNAs represent interesting targets for new therapies because their altered expression influences tumor development and progression. miR-17 is a prototype of onco-miRNA, known to be overexpressed in B-cell non-Hodgkin lymphoma (B-NHL) with peculiar clinic-biological features. AntagomiR molecules have been largely studied to repress the regulatory functions of up-regulated onco-miRNAs, but their clinical use is mainly limited by their rapid degradation, kidney elimination and poor cellular uptake when injected as naked oligonucleotides. Methods: To overcome these problems, we exploited CD20 targeted chitosan nanobubbles (NBs) for a preferential and safe delivery of antagomiR17 to B-NHL cells. Results: Positively charged 400 nm-sized nanobubbles (NBs) represent a stable and effective nanoplatform for antagomiR encapsulation and specific release into B-NHL cells. NBs rapidly accumulated in tumor microenvironment, but only those conjugated with a targeting system (antiCD20 antibodies) were internalized into B-NHL cells, releasing antagomiR17 in the cytoplasm, both in vitro and in vivo. The result is the down-regulation of miR-17 level and the reduction in tumor burden in a human-mouse B-NHL model, without any documented side effects. Discussion: Anti-CD20 targeted NBs investigated in this study showed physico-chemical and stability properties suitable for antagomiR17 delivery in vivo and represent a useful nanoplatform to address B-cell malignancies or other cancers through the modification of their surface with specific targeting antibodies.